The 2012 sandy hook elementary school shooting: Connecticut's department of mental health crisis response. (2nd October 2018) - DiLeo, Paul; Rowe, Michael; Bugella, Barbara; Siembab, Lauren; Siemianowski, James; Black, Jennifer; Rehmer, Patricia; Baker, Frank; Morris, Christa; Delphin-Rittmon, Miriam; Styron, Thomas
ABSTRACT: This article reports on the role, activities, and lessons learned of a state mental health authority—the Connecticut Department of Mental Health and Addiction Services—in responding to the mental health needs of families and community members following the 2012 Sandy Hook Elementary School shooting. Following the introduction, we provide a brief case study of Department of Mental Health and Addiction Services' role in the aftermath of the Sandy Hook shooting. This role included use of the Incident Command System (ICS) to deploy a standing statewide network of clinicians who provided direct care for surviving children and school personnel, victims' family members, and others, and coordination of its mental health response with the activities of other state, private, and individual players. We then discuss key themes and lessons learned and offer recommendations to mental health authorities for planning and implementing their own responses to possible like incidents in the future.